Diphenyl‐2‐pyridylamine‐Substituted Porphyrins as Hole‐Transporting Materials for Perovskite Solar Cells. Issue 19 (21st September 2017) - Lee, Un‐Hak; Azmi, Randi; Sinaga, Septy; Hwang, Sunbin; Eom, Seung Hun; Kim, Tae‐Wook; Yoon, Sung Cheol; Jang, Sung‐Yeon; Jung, In Hwan
Abstract: The susceptibility of porphyrin derivatives to light‐harvesting and charge‐transport operations have enabled these materials to be employed in solar cell applications. The potential of porphyrin derivatives as hole‐transporting materials (HTMs) for perovskite solar cells (PSCs) has recently been demonstrated, but knowledge of the relationships between the porphyrin structure and device performance remains insufficient. In this work, a series of novel zinc porphyrin (PZn) derivatives has been developed and employed as HTMs for low‐temperature processed PSCs. Key to the design strategy is the incorporation of an electron‐deficient pyridine moiety to down‐shift the HOMO levels of porphyrin HTMs. The porphyrin HTMs incorporating diphenyl‐2‐pyridylamine (DPPA) have HOMO levels that are in good agreement with the perovskite active layers, thus facilitating hole transfers from the perovskite to the HTMs. The DPPA‐containing zinc porphyrin‐based PSCs gave the best performance, with efficiency levels comparable to those of PSCs using spiro‐OMeTAD, a current state‐of‐the‐art HTM. In particular, PZn–DPPA‐based PSCs show superior air stability, in both doped and undoped forms, to spiro‐OMeTAD based devices. Abstract : A hole new world : A series of porphyrin‐based hole‐transporting materials (HTMs) has been developed for low‐temperature perovskite solar cells (PSCs). Diphenyl‐2‐pyridylamine (DPPA)‐substituted porphyrin HTM provides high hole mobility and well‐matched energy levels with MAPbI3 perovskite active layers, which improve the charge‐extraction properties of PSCs, demonstrating performances comparable to those of spiro‐OMeTAD‐based devices.